2021
DOI: 10.1097/cce.0000000000000559
|View full text |Cite
|
Sign up to set email alerts
|

Interhospital Transfer Outcomes for Critically Ill Patients With Coronavirus Disease 2019 Requiring Mechanical Ventilation

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 35 publications
3
21
1
Order By: Relevance
“…A case series of six COVID‐19 patients with severe ARDS whose lungs were mechanically ventilated and were evacuated via amphibious assault ship, reported no significant change in P/F ratio post‐transfer [17]. Data from the USA also confirmed that inter‐hospital evacuation of COVID‐19 patients whose lungs were mechanically ventilated did not increase mortality [18]. Previous data in transfer of non‐COVID ARDS patients are, similarly, sparse.…”
Section: Discussionmentioning
confidence: 99%
“…A case series of six COVID‐19 patients with severe ARDS whose lungs were mechanically ventilated and were evacuated via amphibious assault ship, reported no significant change in P/F ratio post‐transfer [17]. Data from the USA also confirmed that inter‐hospital evacuation of COVID‐19 patients whose lungs were mechanically ventilated did not increase mortality [18]. Previous data in transfer of non‐COVID ARDS patients are, similarly, sparse.…”
Section: Discussionmentioning
confidence: 99%
“…Australians critically unwell with COVID‐19 were transferred between hospitals at different stages of the pandemic, typically to provide access to higher level care, because clinical demand was unevenly distributed, or particular hospitals were under strain. The impact of inter‐hospital transfer on clinical outcomes for people with COVID‐19 has been examined overseas; 3‐6 in France, for example, inter‐hospital transfer was associated with a lower risk‐adjusted probability of dying in hospital 4,5 . Investigating its impact in Australia is particularly important, given the critical role played by inter‐hospital transfers in the health care system.…”
mentioning
confidence: 99%
“…As the authors notice, the main result is somewhat surprising as higher mortality has not been reported in recent literature [ 2 , 3 ]. Reasons could be explained as follow: first, the authors specify that 20% of capacity transfers occurred at night, involving severe critically ill patients with acute lung injury, sepsis, and cardiogenic shock.…”
mentioning
confidence: 85%
“…Assuming that interhospital transfers are unsafe and choosing a strategy of implementation of new ICU beds to face surge of critically ill patients could lead to a higher mortality [ 7 ]. During the first months of the COVID-19 crisis, countries planned and organized large-scale interhospital transfers either for clinical or capacity reasons and demonstrated that transferred patients did not have a higher mortality rate [ 2 , 3 , 8 ]. However, we agree with the authors and acknowledge that “understanding the impact of ICU-to-ICU transfer on patient outcome is complex and must consider a couple of important aspects” such as identifying appropriate control patients.…”
mentioning
confidence: 99%